High-adhesiveness composite material for rubber dam and preparation method of high-adhesiveness composite material
By using weather-resistant protective layer, reinforcement layer and self-healing layer of high-adhesive composite materials in rubber dams, the problem of crack propagation in the external environment is solved, and the self-repair of the material and structural stability are improved.
Patent Information
- Application Number
- CN202510709473.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-08-26
- Estimated Expiration
- 2045-05-29
AI Technical Summary
Rubber dams are prone to tiny cracks when exposed to the external environment for a long time. The cracks will expand over time, resulting in structural damage. The existing technology lacks an effective self-repair mechanism.
Highly adhesive composite materials are used, including weather-resistant protective layer, intermediate reinforcement layer and inner self-healing layer. By using high-saturated nitrile rubber and nanoTiO2 with low double bond content in the weather-resistant protective layer, ethylene propylene rubber and aramid fiber are used in the reinforcement layer, silicone rubber and nanoSiO2 particles are used in the self-healing layer to form a three-dimensional network structure and self-healing mechanism to prevent cracks from spreading and perform self-repairing.
Significantly reduces oxidative degradation caused by ozone and ultraviolet rays, improves the tensile strength and tear resistance of the material, provides high elasticity and flexibility, and can repair tiny cracks in a timely manner and prevent further cracks from spreading.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rubber dams, and in particular to a high-adhesion composite material for rubber dams, a preparation method and application thereof. Background Art
[0002] As an important hydraulic engineering structure, rubber dams are widely used in various fields, including water flow regulation, flood control, irrigation, and power generation. Due to their novel design, attractive appearance, simple structure, easy management, short construction period, low investment, and rapid effectiveness, they have been widely used and rapidly developed in various hydraulic engineering fields, including water conservancy, hydropower, water transportation, moisture control, and environmental beautification. Compared with traditional earth, stone, steel, and wood dams, rubber dams offer advantages such as low cost, material conservation, short construction period, excellent seismic resistance, and effective water-stopping.
[0003] The Chinese invention patent application with publication number CN112252276A discloses a movable water-injected rubber dam, which includes a high-strength fiber skeleton, a vulcanized rubber layer, a water injection port, a drainage port and an anchoring mechanism. The dam bag as a whole is similar to an inverted trapezoid, and a high-strength fiber skeleton is arranged inside it. The surface of the high-strength fiber skeleton is covered with multiple layers of vulcanized rubber layers. A water injection device is provided on the upper part of the rubber dam, and the water injection port is connected to an external water injection mechanism. A drainage device is provided at the bottom of the rubber dam, and anchoring mechanisms are provided on both sides of the rubber dam for anchoring or connection.
[0004] The invention proposes a removable, water-filled rubber dam with a simple structure and strong practicality. Its internal high-strength fiber skeleton is wear-resistant and durable. Its unique construction not only provides water resistance but also allows for traffic flow. However, prolonged exposure of these rubber dams to the external environment can cause the rubber molecular chains to break due to ultraviolet radiation, leading to photooxidation and cracking of the rubber surface. These microcracks then expand over time. Ozone in the external environment easily reacts with double bonds in the rubber, causing microcracks to expand. Contaminants in water (such as oils, acids, bases, and chloride ions) can penetrate the rubber, disrupting the crosslinking structure and reducing its toughness. Initially, these microcracks are prone to forming, which then expand into larger cracks as contaminants accumulate. Diurnal and seasonal temperature fluctuations cause the rubber dam material to expand and contract, and repeated deformation can also cause cracks. Cold conditions reduce rubber's elasticity and increase its brittleness, making microcracks more likely to form at weak points when filled with water. In summary, there are many reasons for the occurrence of micro cracks in rubber dams. External stress or aging can cause micro cracks, and it is difficult to completely avoid them. As time goes by, micro cracks will further expand. Therefore, it is particularly important for rubber dams to have self-repair functions when micro cracks appear. Summary of the Invention
[0005] In order to solve the above technical problems, the present invention provides a high-adhesion composite material for rubber dams and a preparation method thereof. The high-adhesion composite material for rubber dams of the present invention has good adhesion and can promptly repair small cracks by itself to prevent further expansion of the cracks.
[0006] In a first aspect, the present invention provides a high-adhesion composite material for a rubber dam, wherein the high-adhesion composite material for the rubber dam comprises an outer weather-resistant protective layer, a middle reinforcement layer, and an inner self-repairing layer. The weather-resistant protective layer comprises, by mass, 90-110 parts of highly saturated nitrile rubber, 23-28 parts of carbon black N550, 3-8 parts of nano-TiO2, 1-3 parts of antioxidant 1010, and 2-3 parts of dicumyl peroxide; the reinforcement layer comprises 60-80 parts of EPDM rubber, 25-35 parts of styrene-butadiene rubber, 13-15 parts of nylon fiber, 10-12 parts of aramid fiber, 12-15 parts of carbon black, 0.5-1.5 parts of graphene, 1-2 parts of sulfur, and 0.5-1.5 parts of accelerator CZ; and the self-repairing layer comprises 90-100 parts of silicone rubber, 5-10 parts of nano-SiO2, 5-8 parts of self-repairing agent, and 0.1-0.3 parts of dispersant.
[0007] In this technical solution, the highly saturated nitrile rubber in the weatherproof protective layer has an extremely low double bond content, significantly reducing oxidative degradation caused by ozone and UV rays. Dicumyl peroxide decomposes at high temperatures to produce free radicals, which trigger crosslinking reactions between the highly saturated nitrile rubber molecular chains. By forming a three-dimensional network structure, the material's tensile strength, elastic modulus, and deformation resistance are enhanced. Carbon black particles absorb and scatter UV rays, reducing photooxidation and delaying rubber aging. Nano-TiO2 photocatalytically decomposes surface organic matter (such as algae) while reflecting UV rays, reducing photodegradation.
[0008] In the reinforcement layer, EPDM rubber offers strong aging resistance, while aramid fibers offer high tensile strength, bearing the primary tensile stress and preventing excessive deformation of the dam. Nylon fibers absorb impact energy and slow crack propagation through plastic deformation, forming a reinforcing network with the aramid fibers. Graphene forms a three-dimensional network within the EPDM and SBR matrix, hindering crack propagation through a "crack pinning effect," enhancing tear resistance and improving thermal conductivity to prevent localized overheating.
[0009] Silicone rubber, the main component of the self-healing layer, provides high elasticity and flexibility to accommodate the dam's deformation requirements. Nano-SiO2 particles dispersed within the silicone rubber matrix inhibit low-temperature embrittlement of the molecular chains through physical crosslinking, enhancing the material's elasticity at low temperatures and improving the hardness and wear resistance of the rubber matrix. The nano-SiO2 particles also work in conjunction with the self-healing agent to slow crack propagation, buying time for self-repair.
[0010] Optionally, the self-healing agent is a microcapsule self-healing agent, which includes 30-32% by mass of a core material, 68-70% by mass of a wall material, and 0.2-0.3% by mass of an emulsifier. The core material includes liquid polysulfide rubber, nano-ZnO, and a silane coupling agent. The mass ratio of the liquid polysulfide rubber, nano-ZnO, and silane coupling agent is 8-10:1:0.1-0.2. The wall material includes urea, formaldehyde, ammonium chloride, and water. The mass ratio of the urea, formaldehyde, ammonium chloride, and water is 1:1.2-1.5:0.05-0.1:9-10.
[0011] In the above technical solution, the stress at the crack tip during crack propagation triggers the rupture of the microcapsules, releasing liquid polysulfide rubber and nano-ZnO modified with a silane coupling agent. The modified nano-ZnO acts as a cross-linking catalyst, reacting with the liquid polysulfide rubber to form a polysulfide network (-SS- bond), which quickly fills the microcracks.
[0012] Optionally, the nylon fiber is a modified nylon fiber, and the preparation steps of the modified nylon fiber are as follows: 5% silane coupling agent is mixed with 95% ethanol, 1% acetic acid is added to adjust the pH to 4-5, the nylon fiber is immersed in the treatment solution, stirred at a constant temperature of 50-70°C for 1-3 hours, dried at 75-85°C for 1-2 hours, and then vacuumed to 10 -2 After the Pa, oxygen is introduced, and the plasma bombards the nylon fiber surface for 3-7 minutes at a power of 45-55 W and a gas flow rate of 18-22 sccm to obtain the modified nylon fiber.
[0013] In the above technical solution, the nylon fiber is treated with a silane coupling agent and plasma, and the surface polar groups (-NH2, -OH) form chemical bonds with the rubber matrix, preventing interlayer peeling, improving the chemical bonding with the rubber, and improving the adhesion of the composite material.
[0014] Optionally, the silicone rubber is a modified silicone rubber, and the preparation steps of the modified silicone rubber are as follows: methyl vinyl silicone rubber and 3-aminopropyltrimethoxysilane are added to toluene and reacted at 75-85°C for 5-7h, the mass ratio of the methyl vinyl silicone rubber to 3-aminopropyltrimethoxysilane is 18-22:1, and then bismaleimide is added and mixed at a mass ratio of 10-12:1, stirred for 3-7min until completely dissolved, and placed in a 55-60°C oven to dry for 1-2h to obtain the modified silicone rubber.
[0015] In this technical solution, 3-aminopropyltrimethoxysilane hydrolyzes to form -Si-O- bonds, introducing furan groups into the silicone rubber network. Bismaleimide (a dienophile) then slowly undergoes a diene addition reaction with the furan groups (dienophiles) in the silicone rubber at room temperature, forming reversible crosslinks. When the temperature rises above 60°C, the reversible crosslinks dissociate, softening the material and causing molecular rearrangement at the crack interface. Upon cooling, the reversible crosslinks reform, restoring the crosslink network and closing the crack.
[0016] In a second aspect, the present invention provides a method for preparing a high-adhesion composite material for a rubber dam, the preparation method comprising the following steps: Preparation of weather-resistant protective layer: Highly saturated nitrile rubber is masticated at 75-85°C for 1-3 minutes, carbon black, nano-TiO2, and antioxidant 1010 are added in sequence, and mixed at 55-65 rpm for 8-12 minutes. Dicumyl peroxide is then added and mixed for another 3-7 minutes. The sheet is then discharged and cooled. Preparation of the reinforcement layer: EPDM rubber and styrene-butadiene rubber are masticated at 65-70°C for 1-5 minutes, carbon black and graphene are added and kneaded at 45-55 rpm for 8-12 minutes, nylon fiber and aramid fiber with a length of 6-8 mm are added and kneaded for 3-7 minutes, sulfur and accelerator CZ are added, and kneaded for 3-7 minutes before discharging; Preparation of self-repairing layer: Thinly pass silicone rubber 2-3 times at 20-30℃, add nano-SiO2 and mix evenly, stir at 100-150rpm, finally add self-repairing agent and dispersant, and slowly stir for 3-5 minutes to ensure uniform dispersion; Vacuum hot pressing vulcanization: Lay each layer of rubber material into the mold in sequence, spray water-based polyurethane adhesive between each layer, pre-bake at 75-85℃ for 3-7 minutes, pre-press at 4-6MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the reinforcement layer, and finally cool to 130℃ to vulcanize the weather-resistant protective layer, maintain pressure and cool to 50℃ for demoulding to obtain a highly adhesive composite material.
[0017] In the above technical solution, bubbles are prone to becoming crack sources. Vacuum can help remove bubbles between layers and prevent weak interfacial bonding. The -NCO groups in the waterborne polyurethane adhesive molecular chain react with the -OH and -NH2 groups on the rubber surface to form chemical bonds.
[0018] Optionally, the preparation method further includes the step of preparing a microcapsule self-repairing agent, and the step of preparing the microcapsule self-repairing agent is as follows: Preparation of the core material: Nano-ZnO is mixed with a silane coupling agent, added to anhydrous ethanol, ultrasonically dispersed at 35-45kHz for 25-35 minutes, stirred at 55-65°C for 1-3 hours, centrifuged at 3500-4500 rpm for 8-12 minutes, washed with ethanol 2-3 times, and vacuum dried at 55-65°C to obtain modified ZnO. The modified ZnO is then mixed with liquid polysulfide rubber and magnetically stirred at 45-55°C and 450-550 rpm for 0.5-1.5 hours to form a uniform suspension. Preparation of wall material: Add urea and formaldehyde into water and stir, adjust the pH to 8.0-8.5, react at 65-75℃ for 0.5-1.5h to generate transparent urea-formaldehyde prepolymer, and cool to room temperature; In-situ polymerization of microcapsules: add the suspension to the urea-formaldehyde prepolymer solution, add an emulsifier, emulsify at 10,000-11,000 rpm for 8-12 minutes to form an emulsion, add ammonium chloride to the emulsion, adjust the pH to 3.0-3.5, stir at a constant temperature of 250-350 rpm and 50-60°C for 2-4 hours, centrifuge at 2,500-3,500 rpm for 3-7 minutes, take the precipitate, wash it with deionized water 2-3 times, and vacuum dry it at 35-45°C for 22-26 hours to obtain a microcapsule self-healing agent.
[0019] In this technical solution, a silane coupling agent hydrolyzes in ethanol to form silanol (-Si(OH)3). This silanol condenses with hydroxyl groups (-OH) on the ZnO surface to form a Si-O-Zn covalent bond. Simultaneously, amino groups (-NH2) are introduced onto the ZnO surface. These amino groups enhance the compatibility of ZnO with polysulfide rubber (containing -SH), preventing nanoparticle agglomeration and ensuring homogeneous dispersion of the core material. The amino groups on the ZnO surface modified with the silane coupling agent hydrogen bond with the thiol groups (-SH) on the liquid polysulfide rubber, forming a stable complex. During the self-healing process, the modified ZnO acts as a cross-linking catalyst, reacting with the liquid polysulfide rubber to form a polysulfide network (-SS- bonds), enabling rapid repair.
[0020] Urea and formaldehyde first generate intermediates such as monomethylol urea and dimethylol urea. Under alkaline conditions, the methylol urea further condenses to form a water-soluble low molecular weight linear urea-formaldehyde resin prepolymer.
[0021] Emulsifiers such as sodium lauryl sulfate, as anionic surfactants, are adsorbed on the interface between the oil phase (liquid polysulfide rubber / modified ZnO) and the water phase to reduce interfacial tension. The sulfonic acid group (-SO3 - ) makes the surface of the emulsion droplets negatively charged, preventing the droplets from coalescing through electrostatic repulsion. The high-speed shearing at 10,000 rpm breaks the oil phase into tiny droplets. Ammonium chloride is hydrolyzed to generate H +, lowering the pH, activating the condensation reaction of hydroxymethyl urea, cross-linking the linear prepolymer into a three-dimensional network structure, and gradually depositing on the surface of the core material droplets to form a dense wall material.
[0022] In a third aspect, the present invention provides a rubber dam using the aforementioned high-adhesion composite material for rubber dams or a high-adhesion composite material prepared using the aforementioned method for preparing the high-adhesion composite material for rubber dams.
[0023] In a fourth aspect, the present invention provides a rubber dam for use in river management industry, agricultural irrigation industry, flood control and tide prevention industry, shipping and transportation industry, and in rubber dam construction in high water pressure environment.
[0024] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The double bond content of highly saturated nitrile rubber in the weather-resistant protective layer is extremely low, which significantly reduces the oxidative degradation caused by ozone and ultraviolet rays. The carbon black particles absorb and scatter ultraviolet rays, reduce photooxidation reactions, and delay rubber aging. Nano-TiO2 decomposes surface organic matter (such as algae) through photocatalysis, while reflecting ultraviolet rays to reduce photodegradation.
[0025] 2. In the reinforcement layer, the EPDM rubber exhibits strong aging resistance, while the aramid fiber exhibits high tensile strength, bearing the primary tensile stress and preventing excessive deformation of the dam. Modified nylon fiber absorbs impact energy, delaying crack propagation through plastic deformation, and forms a reinforcing network with the aramid fiber. Graphene forms a three-dimensional network within the EPDM and SBR matrix, hindering crack propagation through a "crack pinning effect," enhancing tear resistance and improving thermal conductivity to prevent localized overheating.
[0026] 3. In the self-healing layer, modified silicone rubber, as the main component, provides high elasticity and flexibility to adapt to the deformation requirements of the dam. Nano-SiO2 particles are dispersed in the modified silicone rubber matrix. Through physical crosslinking points, they inhibit the low-temperature embrittlement of the molecular chain, enhance the material's elasticity at low temperatures, and improve the hardness and wear resistance of the rubber matrix. Nano-SiO2 particles can also be combined with microcapsule self-healing agents to delay crack propagation and buy time for self-healing. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below with reference to the examples.
[0028] The materials used in the following examples can all be purchased from the market.
[0029] Example 1: This example discloses a high-adhesion composite material #1 for rubber dams and a preparation method thereof.
[0030] The high-adhesion composite material used for the rubber dam includes an outer weather-resistant protective layer, a middle reinforcement layer, and an inner self-repairing layer. Calculated by mass percentage, the weather-resistant protective layer includes 90 parts of highly saturated nitrile rubber, 23 parts of carbon black N550, 3 parts of nano-TiO2, 2 parts of antioxidant 1010, and 2 parts of diisopropylbenzene peroxide; the reinforcement layer includes 60 parts of EPDM rubber, 25 parts of styrene-butadiene rubber, 13 parts of nylon fiber, 12 parts of aramid fiber, 15 parts of carbon black, 0.5 parts of graphene, 1 part of sulfur, and 0.5 parts of accelerator CZ; the self-repairing layer includes 90 parts of silicone rubber, 5 parts of nano-SiO2, 5 parts of self-repairing agent, and 0.1 part of dispersant.
[0031] The self-healing agent comprises epoxidized natural rubber, ZnO, stearic acid, and sulfur in a mass ratio of 100:5:1:1.6. In this embodiment, the dispersant is polyethylene glycol. In other embodiments, the dispersant may also be polyvinyl pyrrolidone, sorbitan monooleate, or other dispersants. The silicone rubber is methyl vinyl silicone rubber.
[0032] The preparation method comprises the following steps: S1. Preparation of weather-resistant protective layer: Highly saturated nitrile rubber was plasticized at 80°C for 2 minutes, carbon black, nano-TiO2, and antioxidant 1010 were added in sequence, and mixed at 60 rpm for 10 minutes. Dicumyl peroxide was then added and mixed for 5 minutes. The sheet was then discharged and cooled.
[0033] S2. Preparation of reinforcement layer: EPDM rubber and styrene-butadiene rubber were plasticized at 68°C for 3 min, carbon black and graphene were added and mixed at 50 rpm for 10 min, nylon fiber and aramid fiber with a length of 6-8 mm were added and mixed for 5 min, sulfur and accelerator CZ were added, and the material was discharged after mixing for 5 min.
[0034] S3. Preparation of self-healing layer: Silicone rubber was thinly passed through the tube three times at 25°C, nano-SiO2 was added and mixed, and the mixture was stirred at 150 rpm. Finally, the self-healing agent and dispersant were added and the mixture was slowly stirred for 2 minutes to ensure uniform dispersion.
[0035] S4. Vacuum hot pressing and vulcanization: Lay each layer of rubber material into the mold in order, spray water-based polyurethane adhesive between each layer, pre-bake at 80℃ for 5 minutes, pre-press at 5MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the reinforcement layer, and finally cool to 130℃ to vulcanize the weather-resistant protective layer, maintain pressure and cool to 50℃ for demoulding to obtain high-adhesion composite material #1.
[0036] Example 2: This example discloses a high-adhesion composite material #2 for rubber dams and a preparation method thereof.
[0037] The high-adhesion composite material for the rubber dam includes an outer weather-resistant protective layer, a middle reinforcement layer, and an inner self-repairing layer. The weather-resistant protective layer comprises, by mass percentage, 110 parts of highly saturated nitrile rubber, 28 parts of carbon black N550, 8 parts of nano-TiO2, 3 parts of antioxidant 1010, and 3 parts of dicumyl peroxide. The reinforcement layer comprises 80 parts of EPDM rubber, 35 parts of styrene-butadiene rubber, 14 parts of nylon fiber, 11 parts of aramid fiber, 15 parts of carbon black, 1.5 parts of graphene, 2 parts of sulfur, and 1.5 parts of accelerator CZ. The self-repairing layer comprises 95 parts of silicone rubber, 6 parts of nano-SiO2, 7 parts of a self-repairing agent, and 0.3 parts of polyethylene glycol. The remaining components are the same as in Example 1.
[0038] The preparation method of high-adhesion composite material #2 for rubber dam is the same as that of Example 1.
[0039] Example 3: This example discloses a high-adhesion composite material #3 for rubber dams and a preparation method thereof.
[0040] The high-adhesion composite material for the rubber dam includes an outer weather-resistant protective layer, a middle reinforcement layer, and an inner self-repairing layer. The weather-resistant protective layer comprises, by mass percentage, 100 parts of highly saturated nitrile rubber, 25 parts of carbon black N550, 5 parts of nano-TiO2, 2 parts of antioxidant 1010, and 2.5 parts of dicumyl peroxide. The reinforcement layer comprises 70 parts of EPDM rubber, 30 parts of styrene-butadiene rubber, 15 parts of nylon fiber, 10 parts of aramid fiber, 15 parts of carbon black, 1 part of graphene, 1.5 parts of sulfur, and 1 part of accelerator CZ. The self-repairing layer comprises 100 parts of silicone rubber, 8 parts of nano-SiO2, 8 parts of a self-repairing agent, and 0.2 parts of polyethylene glycol. The remaining components are the same as in Example 1.
[0041] The preparation method of high-adhesion composite material #3 for rubber dam is the same as that of Example 1.
[0042] Example 4: This example discloses a high-adhesion composite material #4 for rubber dams and a preparation method thereof.
[0043] The high-adhesion composite material used for the rubber dam includes an outer weather-resistant protective layer, a middle reinforcement layer, and an inner self-repairing layer. Calculated by mass percentage, the weather-resistant protective layer includes 100 parts of highly saturated nitrile rubber, 25 parts of carbon black N550, 5 parts of nano-TiO2, 2 parts of antioxidant 1010, and 2.5 parts of diisopropylbenzene peroxide; the reinforcement layer includes 70 parts of EPDM rubber, 30 parts of styrene-butadiene rubber, 15 parts of nylon fiber, 10 parts of aramid fiber, 15 parts of carbon black, 1 part of graphene, 1.5 parts of sulfur, and 1 part of accelerator CZ; the self-repairing layer includes 100 parts of silicone rubber, 8 parts of nano-SiO2, 8 parts of microcapsule self-repairing agent, and 0.2 parts of polyethylene glycol.
[0044] The microcapsule self-healing agent includes 31.5% by mass of a core material, 68.25% by mass of a wall material, and 0.25% by mass of sodium lauryl sulfate. The core material includes liquid polysulfide rubber, nano-ZnO, and a KH-550 coupling agent. The mass ratio of the liquid polysulfide rubber, nano-ZnO, and KH-550 coupling agent is 10:1:0.2. The wall material includes 10 g of urea, 15 g of formaldehyde, 0.5 g of ammonium chloride, and 100 mL of water. The mass ratio of the urea, formaldehyde, ammonium chloride, and water is 1:1.5:0.05:10.
[0045] In this embodiment, sodium lauryl sulfate is selected as the emulsifier, and other emulsifiers may be selected in other embodiments. KH-550 is selected as the silane coupling agent, and other silane coupling agents such as KH-560 may be selected in other embodiments.
[0046] The preparation method comprises the following steps: S1. Preparation of weather-resistant protective layer: Highly saturated nitrile rubber was plasticized at 80°C for 2 minutes, carbon black, nano-TiO2, and antioxidant 1010 were added in sequence, and mixed at 60 rpm for 10 minutes. Dicumyl peroxide was then added and mixed for 5 minutes. The sheet was then discharged and cooled.
[0047] S2. Preparation of reinforcement layer: EPDM rubber and styrene-butadiene rubber were plasticized at 68°C for 3 min, carbon black and graphene were added and mixed at 50 rpm for 10 min, nylon fiber and aramid fiber with a length of 6-8 mm were added and mixed for 5 min, sulfur and accelerator CZ were added, and the material was discharged after mixing for 5 min.
[0048] S3. Preparation of microcapsule self-repairing agent: S31. Preparation of core material: Nano-ZnO was mixed with a silane coupling agent, added to anhydrous ethanol, dispersed by ultrasonication at 40 kHz for 30 min, stirred at 60°C for 2 h, centrifuged at 4000 rpm for 10 min, washed with ethanol three times, and dried under vacuum at 60°C to obtain modified ZnO. The modified ZnO was mixed with liquid polysulfide rubber, and magnetically stirred at 50°C and 500 rpm for 1 h to form a uniform suspension. S32. Preparation of wall material: Add urea and formaldehyde to water and stir, adjust the pH to 8.0-8.5, react at 70°C for 1 hour to generate a transparent urea-formaldehyde prepolymer, and cool to room temperature; S33. In-situ polymerization of microcapsules: add the suspension to the urea-formaldehyde prepolymer solution, add an emulsifier, emulsify at 10,000 rpm for 10 minutes to form an emulsion, add ammonium chloride to the emulsion, adjust the pH to 3.0-3.5, stir at 300 rpm and 55°C for 3 hours, centrifuge at 3,000 rpm for 5 minutes, take the precipitate, wash it with deionized water three times, and vacuum dry it at 40°C for 24 hours to obtain a microcapsule self-healing agent.
[0049] S4. Preparation of self-healing layer: Silicone rubber was thinly passed through the tube three times at 25°C, nano-SiO2 was added and mixed, and the mixture was stirred at 150 rpm. Finally, microcapsule self-healing agent and dispersant were added, and the mixture was slowly stirred for 2 minutes to ensure uniform dispersion.
[0050] S5. Vacuum hot pressing and vulcanization: Lay each layer of rubber material into the mold in order, spray water-based polyurethane adhesive between each layer, pre-bake at 80℃ for 5 minutes, pre-press at 5MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the reinforcement layer, and finally cool to 130℃ to vulcanize the weather-resistant protective layer, maintain pressure and cool to 50℃ for demoulding to obtain high-adhesion composite material #4.
[0051] Example 5: This example discloses a high-adhesion composite material #5 for rubber dams and a preparation method thereof.
[0052] The nylon fiber in this embodiment is modified nylon fiber. The rest is the same as that in Example 3.
[0053] The preparation method comprises the following steps: S1. Preparation of weather-resistant protective layer: Highly saturated nitrile rubber was plasticized at 80°C for 2 minutes, carbon black, nano-TiO2, and antioxidant 1010 were added in sequence, and mixed at 60 rpm for 10 minutes. Dicumyl peroxide was then added and mixed for 5 minutes. The sheet was then discharged and cooled.
[0054] S2. Preparation of modified nylon fiber: 5% silane coupling agent was mixed with 95% ethanol, and 1% acetic acid was added to adjust the pH to 4-5. The nylon fiber was immersed in the treatment solution, stirred at a constant temperature of 60℃ for 2h, dried at 80℃ for 1.5h, and then vacuumed to 10 -2 Pa, oxygen was introduced, and the plasma bombarded the nylon fiber surface for 5 minutes at a power of 50 W and a gas flow rate of 20 sccm to obtain the modified nylon fiber.
[0055] S3. Preparation of reinforcement layer: EPDM rubber and styrene-butadiene rubber were plasticized at 68°C for 3 min, carbon black and graphene were added and mixed at 50 rpm for 10 min, modified nylon fiber and aramid fiber with a length of 6-8 mm were added and mixed for 5 min, sulfur and accelerator CZ were added, and the material was discharged after mixing for 5 min.
[0056] S4. Preparation of self-healing layer: Silicone rubber was thinly passed through the tube three times at 25°C, nano-SiO2 was added and mixed, and the mixture was stirred at 150 rpm. Finally, the self-healing agent and dispersant were added and the mixture was slowly stirred for 2 minutes to ensure uniform dispersion.
[0057] S5. Vacuum hot pressing vulcanization: Lay each layer of rubber material into the mold in order, spray water-based polyurethane adhesive between each layer, pre-bake at 80℃ for 5 minutes, pre-press at 5MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the reinforcement layer, and finally cool to 130℃ to vulcanize the weather-resistant protective layer, maintain pressure and cool to 50℃ for demoulding to obtain high-adhesion composite material #5.
[0058] Example 6: This example discloses a high-adhesion composite material #6 for rubber dams and a preparation method thereof.
[0059] The nylon fiber in this embodiment is modified nylon fiber. The rest is the same as that in Example 4.
[0060] The preparation method comprises the following steps: S1. Preparation of weather-resistant protective layer: Highly saturated nitrile rubber was plasticized at 80°C for 2 minutes, carbon black, nano-TiO2, and antioxidant 1010 were added in sequence, and mixed at 60 rpm for 10 minutes. Dicumyl peroxide was then added and mixed for 5 minutes. The sheet was then discharged and cooled.
[0061] S2. Preparation of modified nylon fiber: 5% silane coupling agent was mixed with 95% ethanol, and 1% acetic acid was added to adjust the pH to 4-5. The nylon fiber was immersed in the treatment solution, stirred at a constant temperature of 60℃ for 2h, dried at 80℃ for 1.5h, and then vacuumed to 10 -2 Pa, oxygen was introduced, and the plasma bombarded the nylon fiber surface for 5 minutes at a power of 50 W and a gas flow rate of 20 sccm to obtain the modified nylon fiber.
[0062] S3. Preparation of reinforcement layer: EPDM rubber and styrene-butadiene rubber were plasticized at 68°C for 3 min, carbon black and graphene were added and mixed at 50 rpm for 10 min, modified nylon fiber and aramid fiber with a length of 6-8 mm were added and mixed for 5 min, sulfur and accelerator CZ were added, and the material was discharged after mixing for 5 min.
[0063] S4. Preparation of microcapsule self-repairing agent: S41. Preparation of core material: Nano-ZnO was mixed with a silane coupling agent, added to anhydrous ethanol, dispersed by ultrasonication at 40 kHz for 30 min, stirred at 60°C for 2 h, centrifuged at 4000 rpm for 10 min, washed with ethanol three times, and dried under vacuum at 60°C to obtain modified ZnO. The modified ZnO was mixed with liquid polysulfide rubber, and magnetically stirred at 50°C and 500 rpm for 1 h to form a uniform suspension. S42. Preparation of wall material: Add urea and formaldehyde to water and stir, adjust the pH to 8.0-8.5, react at 70°C for 1 hour to form a transparent urea-formaldehyde prepolymer, and cool to room temperature; S43. In-situ polymerization of microcapsules: add the suspension to the urea-formaldehyde prepolymer solution, add an emulsifier, emulsify at 10,000 rpm for 10 minutes to form an emulsion, add ammonium chloride to the emulsion, adjust the pH to 3.0-3.5, stir at 300 rpm and 55°C for 3 hours, centrifuge at 3,000 rpm for 5 minutes, take the precipitate, wash it with deionized water three times, and vacuum dry it at 40°C for 24 hours to obtain a microcapsule self-healing agent.
[0064] S5. Preparation of self-healing layer: Thinly pass silicone rubber at 25°C for 3 times, add nano-SiO2 and mix evenly, stir at 150 rpm, finally add microcapsule self-healing agent and dispersant, and slowly stir for 2 minutes to ensure uniform dispersion.
[0065] S6. Vacuum hot pressing vulcanization: Lay each layer of rubber material into the mold in order, spray water-based polyurethane adhesive between each layer, pre-bake at 80℃ for 5 minutes, pre-press at 5MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the reinforcement layer, and finally cool to 130℃ to vulcanize the weather-resistant protective layer, maintain pressure and cool to 50℃ for demoulding to obtain high-adhesion composite material #6.
[0066] Example 7: This example discloses a high-adhesion composite material #7 for rubber dams and its preparation method.
[0067] The silicone rubber of this embodiment is modified silicone rubber. The rest is the same as that of embodiment 3.
[0068] The preparation method comprises the following steps: S1. Preparation of weather-resistant protective layer: Highly saturated nitrile rubber was plasticized at 80°C for 2 minutes, carbon black, nano-TiO2, and antioxidant 1010 were added in sequence, and mixed at 60 rpm for 10 minutes. Dicumyl peroxide was then added and mixed for 5 minutes. The sheet was then discharged and cooled.
[0069] S2. Preparation of reinforcement layer: EPDM rubber and styrene-butadiene rubber were plasticized at 68°C for 3 min, carbon black and graphene were added and mixed at 50 rpm for 10 min, nylon fiber and aramid fiber with a length of 6-8 mm were added and mixed for 5 min, sulfur and accelerator CZ were added, and the material was discharged after mixing for 5 min.
[0070] S3. Preparation of modified silicone rubber: Methyl vinyl silicone rubber and 3-aminopropyltrimethoxysilane were added to toluene and reacted at 80°C for 6 hours. The mass ratio of the methyl vinyl silicone rubber to 3-aminopropyltrimethoxysilane was 20:1. Bismaleimide was then added and mixed at a mass ratio of 10:1. The mixture was stirred for 5 minutes until completely dissolved. The mixture was placed in an oven at 60°C and dried for 1.5 hours to obtain modified silicone rubber.
[0071] S4. Preparation of self-healing layer: Thinly pass the modified silicone rubber at 25°C for 3 times, add nano-SiO2 and mix evenly, stir at 150 rpm, finally add self-healing agent and dispersant, and slowly stir for 2 minutes to ensure uniform dispersion.
[0072] S5. Vacuum hot pressing and vulcanization: Lay each layer of rubber material into the mold in order, spray water-based polyurethane adhesive between each layer, pre-bake at 80℃ for 5 minutes, pre-press at 5MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the reinforcement layer, and finally cool to 130℃ to vulcanize the weather-resistant protective layer, maintain pressure and cool to 50℃ for demoulding to obtain high-adhesion composite material #7.
[0073] Example 8: This example discloses a high-adhesion composite material #8 for rubber dams and its preparation method.
[0074] The silicone rubber of this embodiment is modified silicone rubber. The rest is the same as that of embodiment 4.
[0075] The preparation method comprises the following steps: S1. Preparation of weather-resistant protective layer: Highly saturated nitrile rubber was plasticized at 80°C for 2 minutes, carbon black, nano-TiO2, and antioxidant 1010 were added in sequence, and mixed at 60 rpm for 10 minutes. Dicumyl peroxide was then added and mixed for 5 minutes. The sheet was then discharged and cooled.
[0076] S2. Preparation of reinforcement layer: EPDM rubber and styrene-butadiene rubber were plasticized at 68°C for 3 min, carbon black and graphene were added and mixed at 50 rpm for 10 min, nylon fiber and aramid fiber with a length of 6-8 mm were added and mixed for 5 min, sulfur and accelerator CZ were added, and the material was discharged after mixing for 5 min.
[0077] S3. Preparation of microcapsule self-repairing agent: S31. Preparation of core material: Nano-ZnO was mixed with a silane coupling agent, added to anhydrous ethanol, dispersed by ultrasonication at 40 kHz for 30 min, stirred at 60°C for 2 h, centrifuged at 4000 rpm for 10 min, washed with ethanol three times, and dried under vacuum at 60°C to obtain modified ZnO. The modified ZnO was mixed with liquid polysulfide rubber, and magnetically stirred at 50°C and 500 rpm for 1 h to form a uniform suspension. S32. Preparation of wall material: Add urea and formaldehyde to water and stir, adjust the pH to 8.0-8.5, react at 70°C for 1 hour to generate a transparent urea-formaldehyde prepolymer, and cool to room temperature; S33. In-situ polymerization of microcapsules: add the suspension to the urea-formaldehyde prepolymer solution, add an emulsifier, emulsify at 10,000 rpm for 10 minutes to form an emulsion, add ammonium chloride to the emulsion, adjust the pH to 3.0-3.5, stir at 300 rpm and 55°C for 3 hours, centrifuge at 3,000 rpm for 5 minutes, take the precipitate, wash it with deionized water three times, and vacuum dry it at 40°C for 24 hours to obtain a microcapsule self-healing agent.
[0078] S4. Preparation of modified silicone rubber: Methyl vinyl silicone rubber and 3-aminopropyltrimethoxysilane were added to toluene and reacted at 80°C for 6 hours. The mass ratio of the methyl vinyl silicone rubber to 3-aminopropyltrimethoxysilane was 20:1. Bismaleimide was then added and mixed at a mass ratio of 10:1. The mixture was stirred for 5 minutes until completely dissolved. The mixture was placed in an oven at 60°C and dried for 1.5 hours to obtain modified silicone rubber.
[0079] S5. Preparation of self-healing layer: Thinly pass silicone rubber at 25°C for 3 times, add nano-SiO2 and mix evenly, stir at 150 rpm, finally add microcapsule self-healing agent and dispersant, and slowly stir for 2 minutes to ensure uniform dispersion.
[0080] S6. Vacuum hot pressing and vulcanization: Lay each layer of rubber material into the mold in order, spray water-based polyurethane adhesive between each layer, pre-bake at 80℃ for 5 minutes, pre-press at 5MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the reinforcement layer, and finally cool to 130℃ to vulcanize the weather-resistant protective layer, maintain pressure and cool to 50℃ for demoulding to obtain high-adhesion composite material #8.
[0081] Example 9: This example discloses a high-adhesion composite material #9 for rubber dams and a preparation method thereof.
[0082] The silicone rubber of this embodiment is modified silicone rubber. The rest is the same as that of embodiment 5.
[0083] The preparation method comprises the following steps: S1. Preparation of weather-resistant protective layer: Highly saturated nitrile rubber was plasticized at 80°C for 2 minutes, carbon black, nano-TiO2, and antioxidant 1010 were added in sequence, and mixed at 60 rpm for 10 minutes. Dicumyl peroxide was then added and mixed for 5 minutes. The sheet was then discharged and cooled.
[0084] S2. Preparation of modified nylon fiber: 5% silane coupling agent was mixed with 95% ethanol, and 1% acetic acid was added to adjust the pH to 4-5. The nylon fiber was immersed in the treatment solution, stirred at a constant temperature of 60℃ for 2h, dried at 80℃ for 1.5h, and then vacuumed to 10 -2Pa, oxygen was introduced, and the plasma bombarded the nylon fiber surface for 5 minutes at a power of 50 W and a gas flow rate of 20 sccm to obtain the modified nylon fiber.
[0085] S3. Preparation of reinforcement layer: EPDM rubber and styrene-butadiene rubber were plasticized at 68°C for 3 min, carbon black and graphene were added and mixed at 50 rpm for 10 min, modified nylon fiber and aramid fiber with a length of 6-8 mm were added and mixed for 5 min, sulfur and accelerator CZ were added, and the material was discharged after mixing for 5 min.
[0086] S4. Preparation of modified silicone rubber: Methyl vinyl silicone rubber and 3-aminopropyltrimethoxysilane were added to toluene and reacted at 80°C for 6 hours. The mass ratio of the methyl vinyl silicone rubber to 3-aminopropyltrimethoxysilane was 20:1. Bismaleimide was then added and mixed at a mass ratio of 10:1. The mixture was stirred for 5 minutes until completely dissolved. The mixture was placed in an oven at 60°C and dried for 1.5 hours to obtain modified silicone rubber.
[0087] S5. Preparation of self-healing layer: Thinly pass the modified silicone rubber at 25°C for 3 times, add nano-SiO2 and mix evenly, stir at 150 rpm, finally add self-healing agent and dispersant, and slowly stir for 2 minutes to ensure uniform dispersion.
[0088] S6. Vacuum hot pressing and vulcanization: Lay each layer of rubber material into the mold in order, spray water-based polyurethane adhesive between each layer, pre-bake at 80℃ for 5 minutes, pre-press at 5MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the reinforcement layer, and finally cool to 130℃ to vulcanize the weather-resistant protective layer, maintain pressure and cool to 50℃ for demoulding to obtain high-adhesion composite material #9.
[0089] Example 10: This example discloses a high-adhesion composite material #10 for rubber dams and a preparation method thereof.
[0090] The silicone rubber of this embodiment is modified silicone rubber. The rest is the same as that of Example 6.
[0091] The preparation method comprises the following steps: S1. Preparation of weather-resistant protective layer: Highly saturated nitrile rubber was plasticized at 80°C for 2 minutes, carbon black, nano-TiO2, and antioxidant 1010 were added in sequence, and mixed at 60 rpm for 10 minutes. Dicumyl peroxide was then added and mixed for 5 minutes. The sheet was then discharged and cooled.
[0092] S2. Preparation of modified nylon fiber: 5% silane coupling agent was mixed with 95% ethanol, and 1% acetic acid was added to adjust the pH to 4-5. The nylon fiber was immersed in the treatment solution, stirred at a constant temperature of 60℃ for 2h, dried at 80℃ for 1.5h, and then vacuumed to 10 -2Pa, oxygen was introduced, and the plasma bombarded the nylon fiber surface for 5 minutes at a power of 50 W and a gas flow rate of 20 sccm to obtain the modified nylon fiber.
[0093] S3. Preparation of reinforcement layer: EPDM rubber and styrene-butadiene rubber were plasticized at 68°C for 3 min, carbon black and graphene were added and mixed at 50 rpm for 10 min, modified nylon fiber and aramid fiber with a length of 6-8 mm were added and mixed for 5 min, sulfur and accelerator CZ were added, and the material was discharged after mixing for 5 min.
[0094] S4. Preparation of microcapsule self-repairing agent: S41. Preparation of core material: Nano-ZnO was mixed with a silane coupling agent, added to anhydrous ethanol, dispersed by ultrasonication at 40 kHz for 30 min, stirred at 60°C for 2 h, centrifuged at 4000 rpm for 10 min, washed with ethanol three times, and dried under vacuum at 60°C to obtain modified ZnO. The modified ZnO was mixed with liquid polysulfide rubber, and magnetically stirred at 50°C and 500 rpm for 1 h to form a uniform suspension. S42. Preparation of wall material: Add urea and formaldehyde to water and stir, adjust the pH to 8.0-8.5, react at 70°C for 1 hour to form a transparent urea-formaldehyde prepolymer, and cool to room temperature; S43. In-situ polymerization of microcapsules: add the suspension to the urea-formaldehyde prepolymer solution, add an emulsifier, emulsify at 10,000 rpm for 10 minutes to form an emulsion, add ammonium chloride to the emulsion, adjust the pH to 3.0-3.5, stir at 300 rpm and 55°C for 3 hours, centrifuge at 3,000 rpm for 5 minutes, take the precipitate, wash it with deionized water three times, and vacuum dry it at 40°C for 24 hours to obtain a microcapsule self-healing agent.
[0095] S5. Preparation of modified silicone rubber: Methyl vinyl silicone rubber and 3-aminopropyltrimethoxysilane were added to toluene and reacted at 80°C for 6 hours. The mass ratio of the methyl vinyl silicone rubber to 3-aminopropyltrimethoxysilane was 20:1. Bismaleimide was then added and mixed at a mass ratio of 10:1. The mixture was stirred for 5 minutes until completely dissolved. The mixture was placed in an oven at 60°C and dried for 1.5 hours to obtain modified silicone rubber.
[0096] S6. Preparation of self-healing layer: Thinly pass the modified silicone rubber at 25°C for 3 times, add nano-SiO2 and mix evenly, stir at 150 rpm, finally add microcapsule self-healing agent and dispersant, and slowly stir for 2 minutes to ensure uniform dispersion.
[0097] S7. Vacuum hot pressing and vulcanization: Lay each layer of rubber material into the mold in order, spray water-based polyurethane adhesive between each layer, pre-bake at 80℃ for 5 minutes, pre-press at 5MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the reinforcement layer, and finally cool to 130℃ to vulcanize the weather-resistant protective layer, maintain pressure and cool to 50℃ for demoulding to obtain high-adhesion composite material #10.
[0098] Comparative Example 1: This comparative example provides a high-adhesion composite material D1 for comparison. It is the same as Example 10, except that nitrile rubber is used to replace the highly saturated nitrile rubber in the weather-resistant protective layer, and the weather-resistant protective layer lacks diisopropylbenzene peroxide.
[0099] Comparative Example 2: This comparative example provides a comparative high-adhesion composite material D2 which is the same as Example 10, except that the self-repairing layer does not contain a microcapsule self-repairing agent.
[0100] Comparative Example 3: This comparative example provides a high-adhesion composite material D3 which is the same as Example 10, except that solid polysulfide rubber is used instead of liquid polysulfide rubber.
[0101] Comparative Example 4: This comparative example provides a comparative high-adhesion composite material D4 which is the same as Example 10, except that nano-MgO is used instead of nano-ZnO in the core material of the microcapsule self-healing agent.
[0102] Comparative Example 5: This comparative example provides a comparative high-adhesion composite material D5 that is the same as Example 10, except that the core material of the microcapsule self-healing agent does not include the KH-550 coupling agent.
[0103] Comparative Example 6: This comparative example provides a comparative high-adhesion composite material D6 which is the same as Example 10, except that ammonium sulfate is used instead of ammonium chloride in the wall material of the microcapsule self-healing agent.
[0104] The high-adhesion composite materials #1-#10 of Examples 1-10 and the comparative high-adhesion composite materials D1-D6 of Comparative Examples 1-6 were subjected to a microcrack repair test, a tensile strength recovery rate test (according to ASTM D412 standard), a break elongation recovery rate test, and an interface peeling test. The test results are shown in Table 1.
[0105] Among them, the test steps of the microcrack repair test are as follows: (1) A single crack with a length of 5 mm and a depth of 50 μm was scratched in the middle of the gauge section of each specimen using a diamond blade. The crack width (W0) and depth (D0) were calibrated and measured using a laser confocal microscope with an accuracy of ±0.1 μm. (2) The cracked specimens were placed in an 80°C oven and heated for 1 hour. A slight cyclic load (5% strain, frequency 1 Hz, 10 cycles) was applied to each specimen. (3) The width (W1) and depth (D1) of the cracks after repair were measured using a laser confocal microscope. (4) The following formulas were used for calculation: width repair rate = (1-W0 / W1) × 100%, depth repair rate = (1-D0 / D1) × 100%.
[0106] The steps for testing the tensile strength recovery rate are as follows: test the tensile strength σ0 and σ1 before and after repair according to ASTM D412, and substitute them into the formula for calculation: strength recovery rate = σ0 / σ1×100%.
[0107] The test steps for the elongation at break recovery rate are as follows: Test the tensile strength F0 and F1 before and after repair according to ASTM D412, and substitute them into the formula for calculation: Strength recovery rate = F0 / F1×100%.
[0108] Table 1
[0109] From the data of Examples 1-3, especially the data of Example 3, it can be seen that by rationally proportioning the constituent materials of the high-adhesion composite material of the present application, the high-adhesion composite material for the rubber dam of the present application has excellent microcrack repair rate, tensile strength recovery rate, elongation at break recovery rate, interfacial peeling strength and other properties. The reason is that the double bond content of the highly saturated nitrile rubber in the weather-resistant protective layer is extremely low, which significantly reduces the oxidative degradation caused by ozone and ultraviolet rays. Diisopropylbenzene peroxide can decompose and produce free radicals at high temperatures, triggering a cross-linking reaction between the molecular chains of the highly saturated nitrile rubber, and by forming a three-dimensional network structure, improving the tensile strength, elastic modulus and deformation resistance of the material. In the reinforcement layer, the EPDM rubber has strong aging resistance, and the aramid fiber has a large tensile strength, which can withstand the main tensile stress and prevent the dam body from excessive deformation. Nylon fiber can absorb impact energy, delay crack propagation through plastic deformation, and form a reinforced network with the aramid fiber. Graphene can form a three-dimensional network within the EPDM and SBR matrices, hindering crack propagation through a "crack pinning effect," improving tear resistance while also boosting thermal conductivity and preventing localized overheating. Within the self-healing layer, silicone rubber, as the main component, provides high elasticity and flexibility to accommodate the dam's deformation requirements. Nano-SiO2 particles are dispersed within the modified silicone rubber matrix, inhibiting low-temperature embrittlement of the molecular chains through physical crosslinking points, enhancing the material's elasticity at low temperatures and increasing the hardness and wear resistance of the rubber matrix. The nano-SiO2 particles can also be combined with self-healing agents to slow crack propagation, buying time for self-repair.
[0110] Compared to Example 3, Example 4 employed the present invention's microcapsule self-healing agent. The resulting high-adhesion composite material #4 exhibited further improvements in microcrack repair rate, tensile strength recovery rate, and elongation at break recovery rate. This is because the silane coupling agent in the present invention's microcapsule self-healing agent hydrolyzes in ethanol to form silanol (-Si(OH)3), which condenses with hydroxyl groups (-OH) on the ZnO surface to form Si-O-Zn covalent bonds. Simultaneously, amino groups (-NH2) are introduced onto the ZnO surface. These amino groups enhance the compatibility of ZnO with polysulfide rubber (containing -SH), preventing nanoparticle agglomeration and ensuring homogeneous dispersion of the core material. The amino groups on the ZnO surface, modified with the silane coupling agent, hydrogen bond with the thiol (-SH) groups on the liquid polysulfide rubber, forming a stable composite. During the crack propagation process, the stress at the crack tip triggers the rupture of the microcapsules, releasing liquid polysulfide rubber and modified nano-ZnO. The modified nano-ZnO acts as a cross-linking catalyst and reacts with the liquid polysulfide rubber to form a polysulfide network (-SS- bond), which quickly fills the microcracks.
[0111] Compared with Example 3, Example 5 and Example 6 compared with Example 4, modified nylon fibers were used. The interfacial peel strength of the obtained high-adhesion composite materials #5 and #6 was improved. This is because after the nylon fibers were modified, the polar groups (-NH2, -OH) on the surface can form chemical bonds with the rubber matrix, preventing interlayer peeling, enhancing the chemical bonding with the rubber, and improving the adhesion of the composite materials.
[0112] Compared with Example 3, Example 7, Example 8, Example 4, Example 9, Example 5, and Example 10, Example 6, all use modified silicone rubber. The microcrack repair rate, tensile strength recovery rate, and elongation at break recovery rate of the obtained high-adhesion composite materials #7-#10 are improved. This is because the reversible cross-linking bonds in the modified silicone rubber can dissociate when the temperature is higher than 60°C, softening the material and rearranging the molecules at the crack interface. After cooling, the reversible cross-linking bonds can reorganize and close the cracks.
[0113] Comparative Example 1, compared with Example 10, uses acrylonitrile-butadiene rubber instead of the highly saturated acrylonitrile-butadiene rubber in the weather-resistant protective layer, and the weather-resistant protective layer lacks dicumyl peroxide. The various properties of the resulting high-adhesion composite material D1 have declined to varying degrees. This is because the highly saturated acrylonitrile-butadiene rubber has an extremely low double bond content, which can significantly reduce oxidative degradation caused by ozone and ultraviolet rays. Dicumyl peroxide can decompose at high temperatures to produce free radicals, triggering a cross-linking reaction between the highly saturated acrylonitrile-butadiene rubber molecular chains, and by forming a three-dimensional network structure, improving the material's tensile strength, elastic modulus, and deformation resistance.
[0114] Compared with Example 10, in Comparative Example 2, there is no microcapsule self-healing agent in the self-healing layer, and the various properties of the obtained comparative high-adhesion composite material D2 have dropped significantly. This is because the microcapsule self-healing agent can be triggered by the stress at the crack tip and rupture, releasing liquid polysulfide rubber and modified nano-ZnO. The modified nano-ZnO acts as a cross-linking catalyst, reacting with the liquid polysulfide rubber to form a polysulfide ether network (-SS- bond), which quickly fills the microcracks.
[0115] Compared with Example 10, in Comparative Example 3, solid polysulfide rubber was selected instead of liquid polysulfide rubber, and the various properties of the obtained comparative high-adhesion composite material D3 decreased. This is because the liquid polysulfide rubber contains end groups such as thiol groups (-SH) and can be vulcanized at room temperature, but the solid polysulfide rubber main chain contains sulfur-sulfur bonds, which requires high-temperature vulcanization, and has poor fluidity, and is easily agglomerated with nanoparticles, affecting the homogeneous dispersion of the core material.
[0116] Comparative Example 4 Compared with Example 10, nano-MgO is used instead of nano-ZnO in the core material of the microcapsule self-healing agent. The microcrack repair rate, tensile strength recovery rate, and elongation at break recovery rate of the obtained comparative high-adhesion composite material D4 are all reduced. This is because the vulcanization of liquid polysulfide rubber requires the reaction of thiol groups with metal oxides, and magnesium oxide has a low efficiency in forming a cross-linked structure and cannot replace zinc oxide to play a key role.
[0117] Comparative Example 5 Compared with Example 10, the core material of the microcapsule self-healing agent does not include the KH-550 coupling agent, and the performance of the obtained comparative high-adhesion composite material D5 is reduced. This is because the silane coupling agent is hydrolyzed in ethanol to generate silanol (-Si(OH)3), and the silanol condenses with the hydroxyl group (-OH) on the ZnO surface to form a Si-O-Zn covalent bond. At the same time, amino groups (-NH2) are introduced on the ZnO surface. The amino group improves the compatibility of ZnO and polysulfide rubber (containing -SH), prevents the agglomeration of nanoparticles, and ensures the homogeneous dispersion of the core material.
[0118] Comparative Example 6 Compared with Example 10, ammonium sulfate replaces ammonium chloride in the wall material of the microcapsule self-repairing agent. The performance of the obtained high-adhesion composite material D6 is reduced. This is because ammonium chloride is hydrolyzed to generate H + , lowering the pH and activating the condensation reaction of hydroxymethylurea. Although the hydrolysis of ammonium sulfate also generates an acidic environment, the sulfate ion (SO4 2- ) may form hydrogen bonds or complexes with the hydroxyl groups in hydroxymethylurea, hindering the advancement of the condensation reaction.
[0119] From this we can see that missing or replaced materials cannot play a role in high-adhesion composite materials, but will instead reduce the performance of high-adhesion composite materials. Therefore, each component cannot be arbitrarily replaced by other materials.
[0120] The above are all preferred embodiments of the present invention, and are not intended to limit the scope of protection of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-adhesion composite material for a rubber dam, characterized in that: The high-adhesion composite material for the rubber dam includes an outer weather-resistant protective layer, a middle reinforcement layer, and an inner self-repairing layer. Calculated by mass, the weather-resistant protective layer includes 90-110 parts of highly saturated nitrile rubber, 23-28 parts of carbon black N550, 3-8 parts of nano-TiO2, 1-3 parts of antioxidant 1010, and 2-3 parts of diisopropylbenzene peroxide; the reinforcement layer includes 60-80 parts of EPDM rubber, 25-35 parts of styrene-butadiene rubber, 13-15 parts of nylon fiber, 10-12 parts of aramid fiber, 12-15 parts of carbon black, 0.5-1.5 parts of graphene, 1-2 parts of sulfur, and 0.5-1.5 parts of accelerator CZ; the self-repairing layer includes 90-100 parts of silicone rubber, 5-10 parts of nano-SiO2, 5-8 parts of self-repairing agent, and 0.1-0.3 part of dispersant.
2. The high-adhesion composite material for a rubber dam according to claim 1, characterized in that: The self-repairing agent is a microcapsule self-repairing agent, which includes 30-32% by mass of a core material, 68-70% by mass of a wall material, and 0.2-0.3% by mass of an emulsifier. The core material includes liquid polysulfide rubber, nano-ZnO, and a silane coupling agent. The mass ratio of the liquid polysulfide rubber, nano-ZnO, and silane coupling agent is 8-10:1:0.1-0.
2. The wall material includes urea, formaldehyde, ammonium chloride, and water. The mass ratio of the urea, formaldehyde, ammonium chloride, and water is 1:1.2-1.5:0.05-0.1:9-10.
3. The high-adhesion composite material for a rubber dam according to claim 1 or 2, characterized in that: The nylon fiber is a modified nylon fiber, and the preparation steps of the modified nylon fiber are as follows: 5% silane coupling agent is mixed with 95% ethanol, 1% acetic acid is added to adjust the pH to 4-5, the nylon fiber is immersed in the treatment solution, stirred at a constant temperature of 50-70°C for 1-3 hours, dried at 75-85°C for 1-2 hours, and then vacuumed to 10 -2 After the Pa, oxygen is introduced, and the plasma bombards the nylon fiber surface for 3-7 minutes at a power of 45-55 W and a gas flow rate of 18-22 sccm to obtain the modified nylon fiber.
4. The high-adhesion composite material for a rubber dam according to claim 3, characterized in that: The silicone rubber is a modified silicone rubber. The preparation steps of the modified silicone rubber are as follows: methyl vinyl silicone rubber and 3-aminopropyltrimethoxysilane are added to toluene and reacted at 75-85°C for 5-7 hours, wherein the mass ratio of the methyl vinyl silicone rubber to 3-aminopropyltrimethoxysilane is 18-22:1; bismaleimide is then added and mixed at a mass ratio of 10-12:1; the mixture is stirred for 3-7 minutes until completely dissolved; and the mixture is placed in an oven at 55-60°C and dried for 1-2 hours to obtain the modified silicone rubber.
5. A method for preparing a high-adhesion composite material for a rubber dam according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Preparation of weather-resistant protective layer: Highly saturated nitrile rubber is masticated at 75-85°C for 1-3 minutes, carbon black, nano-TiO2, and antioxidant 1010 are added in sequence, and mixed at 55-65 rpm for 8-12 minutes. Dicumyl peroxide is then added and mixed for another 3-7 minutes. The sheet is then discharged and cooled. Preparation of the reinforcement layer: EPDM rubber and styrene-butadiene rubber are masticated at 65-70°C for 1-5 minutes, carbon black and graphene are added and kneaded at 45-55 rpm for 8-12 minutes, nylon fiber and aramid fiber with a length of 6-8 mm are added and kneaded for 3-7 minutes, sulfur and accelerator CZ are added, and kneaded for 3-7 minutes before discharging; Preparation of self-repairing layer: Thinly pass silicone rubber at 20-30℃ for 2-3 times, add nano-SiO2 and mix evenly, stir at 100-150rpm, finally add self-repairing agent and dispersant, and slowly stir for 3-5min; Vacuum hot pressing vulcanization: Lay each layer of rubber material into the mold in sequence, spray water-based polyurethane adhesive between each layer, pre-bake at 75-85℃ for 3-7 minutes, pre-press at 4-6MPa to exhaust, first raise the temperature to 60℃ to vulcanize the self-repairing layer, then raise the temperature to 150℃ to vulcanize the middle layer, and finally cool to 130℃ to vulcanize the outer layer, maintain pressure and cool to 50℃ for demoulding to obtain a highly adhesive composite material.
6. The method for preparing a high-adhesion composite material for a rubber dam according to claim 5, characterized in that: The preparation method further includes the steps of preparing a microcapsule self-repairing agent, and the steps of preparing the microcapsule self-repairing agent are as follows: Preparation of the core material: Nano-ZnO is mixed with a silane coupling agent, added to anhydrous ethanol, ultrasonically dispersed at 35-45kHz for 25-35 minutes, stirred at 55-65°C for 1-3 hours, centrifuged at 3500-4500 rpm for 8-12 minutes, washed with ethanol 2-3 times, and vacuum dried at 55-65°C to obtain modified ZnO. The modified ZnO is then mixed with liquid polysulfide rubber and magnetically stirred at 45-55°C and 450-550 rpm for 0.5-1.5 hours to form a uniform suspension. Preparation of wall material: Add urea and formaldehyde into water and stir, adjust the pH to 8.0-8.5, react at 65-75℃ for 0.5-1.5h to generate transparent urea-formaldehyde prepolymer, and cool to room temperature; In-situ polymerization of microcapsules: add the suspension to the urea-formaldehyde prepolymer solution, add an emulsifier, emulsify at 10,000-11,000 rpm for 8-12 minutes to form an emulsion, add ammonium chloride to the emulsion, adjust the pH to 3.0-3.5, stir at a constant temperature of 250-350 rpm and 50-60°C for 2-4 hours, centrifuge at 2,500-3,500 rpm for 3-7 minutes, take the precipitate, wash it with deionized water 2-3 times, and vacuum dry it at 35-45°C for 22-26 hours to obtain a microcapsule self-healing agent.
7. A rubber dam, characterized in that: The rubber dam uses the high-adhesion composite material for rubber dams according to any one of claims 1 to 4 or the high-adhesion composite material prepared by the preparation method of the high-adhesion composite material for rubber dams according to any one of claims 5 to 6.
8. Use of the rubber dam according to claim 7 in river regulation, agricultural irrigation, flood control, shipping and transportation, and rubber dam construction under high water pressure.
Citation Information
Patent Citations
Movable water injection type rubber dam
CN112252276A
Double-wall sandwich structural microcapsule self-repairing rubber and preparation method thereof
CN103467791A
Preparation method for composite silicone rubber aging repair liquid
CN105482123A
Self-repairing rubber material and preparation method thereof
CN109111604A
Anti-scratch cut and anti-piercing material, rubber dam and production process of rubber dam
CN110344375A
Cited By
An Integrated Rubber Plate For Rubber Dam And Its Manufacturing Method
KR103000100B1